2013
DOI: 10.1007/s11481-013-9468-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of NMDA Receptor-Mediated Excitatory Postsynaptic Currents by gp120-Treated Macrophages: Implications for HIV-1-Associated Neuropathology

Abstract: A plethora of prior studies has linked HIV-1-infected and immune activated brain mononuclear phagocytes (MP; blood borne macrophages and microglia) to neuronal dysfunction. These are modulated by N-methyl-D-aspartate receptor (NMDAR) antagonists and supporting their relevance for HIV-1-associated nervous system disease. The role of NMDAR subsets in HIV-1-induced neuronal injury, nonetheless, is poorly understood. To this end, we investigated conditioned media from HIV-1gp120-treated human monocyte-derived-macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Further studies unraveled that gp120 increased both EPSC NR2AR and EPSC NR2BR with significant stronger effect on EPSC NR2BR than EPSC NR2AR . Using an experimental protocol to block synaptic NMDARs (Thomas et al, 2006; Yang et al, 2013), we revealed that gp120 significantly increased extra-synaptic EPSC NMDAR which was blocked by a NR2BR antagonist ifenprodil, demonstrating for the first time, to our knowledge, that gp120 acts on extra-synaptic NR2BRs.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Further studies unraveled that gp120 increased both EPSC NR2AR and EPSC NR2BR with significant stronger effect on EPSC NR2BR than EPSC NR2AR . Using an experimental protocol to block synaptic NMDARs (Thomas et al, 2006; Yang et al, 2013), we revealed that gp120 significantly increased extra-synaptic EPSC NMDAR which was blocked by a NR2BR antagonist ifenprodil, demonstrating for the first time, to our knowledge, that gp120 acts on extra-synaptic NR2BRs.…”
Section: Discussionmentioning
confidence: 85%
“…Gp120 is toxic to neural cells and can promote detrimental alterations on synaptic transmission and plasticity, leading to an impairment of cognitive function (Dreyer and Lipton, 1995; Lannuzel et al, 1997; Dong and Xiong, 2006). Studies have shown that gp120 causes neuronal damage through multiple pathways including direct interactions with neurons via cell surface receptors and ion channels (Lannuzel et al, 1995; Medina et al, 1999) or by stimulating mononuclear phagocytes (brain perivascular macrophages and microglia) release of neurotoxic substances, the so-called indirect mechanism, which in turn act on neuronal cells leading to neuronal damage (Xiong et al, 2003; O'Donnell et al, 2006; Yang et al, 2013). It is widely accepted that the major pathway by which gp120 causes neuronal injury is via activation of NMDARs and resultant raising intracellular calcium concentration (Barks et al, 1995; Kaul, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, this approach enables recording from single cells and from networks of many cells simultaneously. In addition to Tat [13, 36], many HIV-associated neurotoxins, while acting through distinct upstream pathways, potentiate NMDAR mediated Ca 2+ influx including: gp120 [20, 3739], inflammatory cytokines [40, 41] and excitotoxins [42]. Thus, results obtained with Tat may extend to other neurotoxins.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to synaptic degeneration, HIV-1 proteins may also interfere with synaptic activity (Haughey and Mattson, 2002; Kasyanov et al , 2006; Krogh et al , 2014; Nath et al , 1996; Tovar et al , 2013; Xu et al , 2011). For instance, gp120 was shown to activate N-methyl D-aspartate receptor (NMDAR), and this could induce synaptic damage (Gemignani et al , 2000; Kaul and Lipton, 1999; Lipton, 1992; Pattarini et al , 1998; Toggas et al , 1996; Viviani et al , 2006; Yang et al , 2013). Interestingly, T-cell-tropic (T-tropic) gp120 IIIB promoted trafficking and surface clustering of NMDA receptors in membrane microdomains in cultured hippocampal neurons.…”
Section: Introductionmentioning
confidence: 99%